Biodiversity loss and conservation in fragmented forest landscapes : the forests of montane Mexico and temperate South America - Newton, Adrian C. (CAB books., 2007)
This book is the result of an international collaborative research effort focusing on the tropical montane forests of Mexico and the temperate rain forests of southern South America. The over-all aim of the research was to investigate the impact of human activity on the key processes influencing biodiversity in fragmented forest landscapes, and to use the research results to develop practical tools for evaluating land use decisions, thereby indicating how sustainable forest management might be achieved in practice.